The improvement of the farm kitchen - Holmberg, Edith Antonette (Kansas State University, 1928)
The purpose or aim of this study is to determine the essentials of an efficient farm kitchen and to show what is being done in Kansas to make the farm kitchen an attractive, convenient, and well equipped workshop.
Keywords: Kitchens--Design and construction.